Factors affecting compliance of drug therapy in outpatient children - Goudar, Vikram R.; Matti, Mahantesh; Kulkarni, Vijay (International Journal of Contemporary Pediatrics, 2019)
Background: Adherence to a medical treatment regimen is an essential determinant of clinical success and professional success of doctor as well. Compared with the thousands of trials for individual drugs and treatments, there are few relatively rigorous trials of adherence interventions. Our study is a small effort towards understanding reasons for poor compliance among paediatric patients. Methods: The 256 cases that were selected for study had various clinical conditions. Compliance definition was applied only for those who received antibiotics. For other cases who received drugs other than antibiotics, we asked number of skipped doses. Data collected by paediatrician during follow-up or next visit because of some other illness and by telephone call to parents by assistant. Parents and kids were asked about the reasons for skipping the doses and also about their personal preferences towards medicines. Results: Out of 256 children 93 were prescribed antibiotics, 37.63% had good compliance and 62.36% had poor compliance.7% never skipped any medicine, 62% skipped less often (≤5 times) and 31% skipped. Very often (≥6 times), taste (67%), quantity (52%), apparent recovery (62%), school (65%), sleeping (56%), timing with food (47%) and bottle getting finished (49%) were the most common reasons for missing the dose of any medicine. Adherence was better when less number of doses were given less often. Chocolate flavor was liked by most kids. Conclusions: Prescribing medications should involve parents, children and practitioners in an open discussion around the most suitable, palatable formulations for successful treatment outcomes.